Genome Mining and Marine Microbial Natural Products - Hong, Kui (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Two review papers, eight research articles, and one brief report were published in this Special Issue. They showed the rich resources that are present within the genomes of marine microorganisms and discussed the use of recently developed tools and technologies to exploit this genetic richness. Examples include the rational supply of precursors according to the relevant biosynthetic pathway and stress driven discovery together with the use of histone deacetylase inhibitors to facilitate the discovery of new bioactive molecules with potential biopharmaceutical applications. We believe that the content of this Special Issue reflects the current state-of-the-art research in this area and highlights the interesting strategies that are being employed to uncover increasing numbers of exciting novel compounds for drug discovery from marine genetic resources.